Assessing the effectiveness of software driven digital therapeutics in patients with coronary artery disease or post coronary intervention: real-world evidence study - Palshikar, Abhijeet A.; Gharat, Chetan; Patel, Kamlesh (International Journal of Advances in Medicine, 2024)
Background: Coronary artery disease (CAD) is a significant health concern worldwide. Acute coronary syndrome (ACS) is a common form of CAD that requires immediate treatment. Digital therapeutics (DTx) have emerged as a promising field for disease management, utilizing remote monitoring and promoting behavioral changes. This study aims to evaluate the effectiveness of LYFE app intervention in improving outcomes for patients with CAD, specifically those with ACS or who have undergone percutaneous coronary intervention (PCI). Methods: This pilot, single-center, real-world evidence study evaluates the effectiveness of the LYFE in CAD and/or post-PCI patients. The primary goal was to assess adherence to medication, physical exercise, diet, and well-being of the participants. Secondary outcomes included assessing vital changes and the incidence of major adverse cardiovascular events over 6 months. Results: Among all participants, the majority were male (93.3%) with a mean age of 53.2±12.1 years. After implementing the LYFE app, 90% adhered to regular exercise, 79.3% to prescribed diet and 79.3% reported that they had no difficulty in remembering medication over 6 months. Additionally, notable improvements were observed in the well-being of the participants using the Dartmouth COOP questionnaire. Furthermore, the intervention significantly reduced SBP (-5.52 mmHg, p=0.038), and DBP (-2.63 mmHg, p=0.044) over 6-month follow-up. By the end of the study, 88.9% of the patients had their blood pressure under control. No cardiovascular death or major bleeding events were reported. Conclusions: LYFE has the potential to enhance cardiovascular health and well-being in CAD and/or post-PCI patients.